Diseño de sistema para extracción de agua potable desde el subsuelo dirigido a la comunidad rural de Arenas Blancas utilizando energía solar fotovoltaica (2022)
This project describes the structure of a water pumping method water extracted from wells, using energy Solar Photovoltaic, with the implementation of water reservoirs or elevated tanks we can eliminate the use of batteries, since we will accumulate water and not electricity making this project or design have lower running and maintenance cost. As well as the presentation of the same and the need for its realization addressed from different points of view, explains the method or strategy to achieve the goals. It should be noted that the project seeks meet the basic need of availability of drinking water and basic sanitation of the rural community of Arenas Blancas, this corregimiento belongs to the municipality of Chiriguaná (Cesar). The area rural area of ​​this corregimiento is two formed and associated by 28 families who live on their plots, far from the urban area, this community does not have basic services such as drinking water for consumption or drinking and energy electricity necessary for the development of many home activities.